Coercive family process and early-onset conduct problems from age 2 to school entry. (2nd April 2014) - Smith, Justin D.; Dishion, Thomas J.; Shaw, Daniel S.; Wilson, Melvin N.; Winter, Charlotte C.; Patterson, Gerald R.
Abstract: The emergence and persistence of conduct problems (CPs) during early childhood is a robust predictor of behavior problems in school and of future maladaptation. In this study we examined the reciprocal influences between observed coercive interactions between children and caregivers, oppositional and aggressive behavior, and growth in parent report of early childhood (ages 2–5) and school-age CPs (ages 7.5 and 8.5). Participants were drawn from the Early Steps multisite randomized prevention trial that includes an ethnically diverse sample of male and female children and their families ( N = 731). A parallel-process growth model combining latent trajectory and cross-lagged approaches revealed the amplifying effect of observed coercive caregiver–child interactions on children's noncompliance, whereas child oppositional and aggressive behaviors did not consistently predict increased coercion. The slope and initial levels of child oppositional and aggressive behaviors and the stability of caregiver–child coercion were predictive of teacher-reported oppositional behavior at school age. Families assigned to the Family Check-Up condition had significantly steeper declines in child oppositional and aggressive behavior and moderate reductions in oppositional behavior in school and in coercion at age 3. Results were not moderated by child gender, race/ethnicity, or assignment to the intervention condition. The implications of these findings are discussed with respect to understanding the early development of CPs and to designing optimal strategies for reducing problem behavior in early childhood with families most in need.